Management Conflict of Pesantren: Political Policy Practices of Pesantren Organizations in Aceh Indonesia - Muhammad Anggung Manumanoso Prasetyo; Feruz Akbarov; Almira Keumala Ulfah; Fadhlur Rahman (Journal of Islamic Civilization, 2024)
Organizational conflicts are intrinsically linked to leadership and political dynamics. This study aims to describe an empirical experience and develop a model of the efficacy of political policy practices in resolving organizational conflicts within pesantren (Islamic boarding schools). The study adopts a qualitative approach, utilizing the diary method based on empirical data gathered from fourteen years (2010-2024) of active and consultative management of a pesantren. The research informants include the most senior leader of the pesantren and several teachers involved in the conflict. Informants were identified using the snowball sampling technique. The findings of this study reveal that the political practices of leadership in managing conflicts within pesantren consist of three strategic steps: the central role of leadership and political acumen, the reinforcement of cultural values within the pesantren through collective commitment, and the effectiveness of the employed conflict resolution strategies. Resolving individual conflicts, particularly those involving teachers and leadership, is essential to prevent the escalation of disputes into open conflicts. Conversely, individual conflicts between teachers and staff often lead to collaboration and compromise. Moreover, institutional conflicts between the pesantren and external parties create a competitive environment in which the pesantren's position must be fortified to ensure legitimacy while minimizing external interference.This research carries significant social implications. If pesantren successfully navigate conflicts, they are likely to benefit the broader community. As religious institutions, pesantren require support, protection, and advocacy.